2010
DOI: 10.1111/j.1476-5381.2010.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of enteric neuromuscular functions by purinergic A3 receptors in normal rat distal colon and experimental bowel inflammation

Abstract: BACKGROUND AND PURPOSEAdenosine A3 receptors mediate beneficial effects in experimental colitis, but their involvement in enteric neuromuscular functions during bowel inflammation is undetermined. This study investigated the regulatory role of A3 receptors on colonic motility in the presence of experimental colitis. EXPERIMENTAL APPROACHColitis was induced in rats by 2,4-dinitrobenzenesulfonic acid. A3 receptors and adenosine deaminase (ADA, adenosine catabolic enzyme) mRNA were examined by RT-PCR. Tissue dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 49 publications
(57 reference statements)
4
43
1
Order By: Relevance
“…In enteric neurons and epithelial cells, the A 3 AR was first evidenced by immunohistochemical studies (Christofi et al, 2001;Antonioli et al, 2010;Ren et al, 2011) and subsequently quantified in colonic mucosa by radioligand binding experiments (Gessi et al, 2004a). The presence of functional A 3 AR has also been demonstrated in human lung parenchyma, in lung type 2 alveolar-like cells (A549), and in bronchi through radioligand binding and immunohistochemical assays Calzetta et al, 2011).…”
Section: Distribution Of the A 3 Adenosine Receptormentioning
confidence: 99%
See 1 more Smart Citation
“…In enteric neurons and epithelial cells, the A 3 AR was first evidenced by immunohistochemical studies (Christofi et al, 2001;Antonioli et al, 2010;Ren et al, 2011) and subsequently quantified in colonic mucosa by radioligand binding experiments (Gessi et al, 2004a). The presence of functional A 3 AR has also been demonstrated in human lung parenchyma, in lung type 2 alveolar-like cells (A549), and in bronchi through radioligand binding and immunohistochemical assays Calzetta et al, 2011).…”
Section: Distribution Of the A 3 Adenosine Receptormentioning
confidence: 99%
“…A 3 ARs are present in immune cells and are involved in the physiopathologic regulation of inflammatory and immune processes mediated by adenosine (Antonioli et al, 2010;Hasko and Cronstein, 2013).…”
Section: Immune System and Inflammationmentioning
confidence: 99%
“…Neural A 3 AR are involved in the regulation of both neuromuscular functions 145 and coordination of motility and secretion in the colon. 146 A 3 AR is distributed throughout myenteric ganglia in the colon, with highest expression in distal colon of the rat.…”
Section: 0 A3 A1 A2a P2x and P2y1 Receptors And Implications Formentioning
confidence: 99%
“…RT-PCR indicated that A 3 and ADA mRNA increased in inflamed tissues from experimental colitis. 145 The A 3 AR – mediated tonic inhibitory control of colonic cholinergic contractions was shown to be impaired in the inflamed bowel despite an increase in functional A 3 AR.…”
Section: 0 A3 A1 A2a P2x and P2y1 Receptors And Implications Formentioning
confidence: 99%
“…Purinergic neuromuscular transmission to the vascular and circular smooth muscle is reduced during experimental colitis in mice and rats (Antonioli et al 2010;Neshat et al 2009;Roberts et al 2012). ACh released from submucosal vasomotor neurons binds to endothelial muscarinic receptors, which stimulates endothelial NO synthase.…”
Section: Effects Of Colitis On the Ensmentioning
confidence: 99%